Effect of micro texture on the performance of cutting tools for aluminium - Durairaj, Shanmugasundaram (Nanyang Technological University, 2020)
Due to environmental obligations on manufacturing industries, there has been a continuous effort to develop new methodologies targeting sustainable manufacturing. One such effort is shifting from flooded lubrication to minimum quantity lubrication and dry machining. It is estimated that almost 25 to 60% of energy is wasted in the tool-chip and tool-workpiece interaction zones. The major loss of energy in the interaction zones is due to friction. The use of lubricants and/or coolants could potentially solve this problem, but practically it is difficult for the fluid to penetrate between the interfaces during machining. To address this problem, micro-texturing of the tool surface has been proposed. This solution can be beneficial in two ways; firstly, the texture acts as a reservoir of lubricants in the interaction zone and secondly, it reduces the actual contact area. Thus, tribological properties are modified by surface texturing and are utilised to improve the performance of the cutting tool by reducing the energy losses due to friction. In this work, surfaces very near to the cutting edge in the rake face of the tool are textured using micro-EDM and laser micromachining. Experimentally it has been demonstrated that textures can be used to improve the cutting performance of the tool in certain conditions. There are many investigations of employing texture tools for the cutting of steels and titanium alloys indicating the beneficial effects of the texture tools. There are few investigations on the cutting of aluminium, although the cutting of aluminium occurs extensively. Due to their differences in material properties, unfortunately, the same conclusion of beneficial outcomes of using a texture tool for cutting of steel and titanium may not be translated directly to aluminium without further investigations. As such, this investigation focuses on the use of texture tool for cutting of aluminium. The rake face textures are found to induce significant improvement in the cutting performances in terms of cutting force decrement and chip morphology. However, such effects are not observed in flank face textures for the tested conditions. The texture effect is further investigated in this thesis under three sections: experimental study, simulation and acoustic emission. In the experimental study, the influence of geometric texture parameters, such as texture shape and size, depth, pitch and distance of the features from the cutting edge, was studied using statistical analysis. The Taguchi methodology of L9 Orthogonal Array was used for the experimental study of four texture parameters at three levels. ANOVA was then used to establish the percentage contributions of significant texture parameters to cutting forces. Furthermore, the Taguchi methodology was used to study the effect of the same texture parameters on other responses, including shear angle, contact area and percentage concentration of workpiece material on the cutting surface. The effect on all the responses was finally compared for the given texture parameters. To understand the effect of micro-texture and its effective utilisation, finite element-based simulation using arbitrary ductile fracture for chip separation was conducted. Abaqus/Explicit software with the Lagrangian formulation was used for the simulation as it is capable of coupling material damage and its fracture energy. Simulation results showed a reduction in cutting forces and similar chip formation characteristics as in the experimental study. It is attributed that the reduction in cutting forces and chip curling effect in the rake textured tools are due to the presence of textures on the rake face, which cause smaller chip tool contact length, reduced friction coefficient and local lubrication effect. The acoustic emission study focusses more on the cutting phenomena involved in the metal cutting process. Cutting involves three phenomena, namely rubbing, ploughing and cutting. Generally, rubbing and ploughing are undesirable effects that cause friction and heat, and thus wastage of energy supplied. The introduction of texture on the cutting tool surface can modify or reduce the amount of these undesirable phenomena. To identify these phenomena which are occurring in the cutting process, Acoustic Emission (AE) signals were used. The signals are extracted from the cutting process for non-textured tools, and the frequencies associated with each phenomenon are determined. The difference in the contribution of each phenomenon to the textured tool is then calculated. Such difference gives a measure of the influence of the texture on the cutting mechanisms, and this can be used to produce more effective textured tools. In summary, the micro-texture effect on the cutting tool was demonstrated experimentally, and the contribution of texture geometry parameters and their distribution was estimated statistically. Furthermore, the FEM simulation study facilitates the understanding of the change in cutting mechanisms with the introduction of texture, which is difficult to observe experimentally. In addition, the utilisation of AE signals in estimating the change in cutting phenomena due to texturing of the cutting tool was proposed and evaluated. Finally, this study gives an overall in-depth analysis of the texture effect in improving the performance of cutting tools on aluminium.